2015
DOI: 10.21608/eajbsf.2015.17237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Essential Oils and /or Gamma Irradiation on the Greater Wax Moth, Galleria Mellonella

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Also, clove oil differed significantly from other oils. Elbarky et al (2015) studied the efficacy of some essential oils viz., peppermint (Mentha piperita L.), geranium (Pelargonium graveolens L.) and basil, O. basilicum, using four concentrations of each oil (0.625, 1.25, 2.50 and 5.0%) against the fourth instar larvae of G. mellonella. They found that basil oil, O. basilicum scored the highest larval mortality (100%), followed by M. piperita (67%), then P. graveolens (50%) at a concentration of 5% after 96 hours of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Also, clove oil differed significantly from other oils. Elbarky et al (2015) studied the efficacy of some essential oils viz., peppermint (Mentha piperita L.), geranium (Pelargonium graveolens L.) and basil, O. basilicum, using four concentrations of each oil (0.625, 1.25, 2.50 and 5.0%) against the fourth instar larvae of G. mellonella. They found that basil oil, O. basilicum scored the highest larval mortality (100%), followed by M. piperita (67%), then P. graveolens (50%) at a concentration of 5% after 96 hours of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sanad and Mohanny (2015) sprayed 4% clove and mint extract on new combs and found that the spray with clove extract reduced the wax moth's life cycle to 42.9 days while untreated combs was 72.0 days. in addition, Elbarky et al (2015) found that the essential oils increased the larval and pulpal periods and decreased pupation and percentage of adult emergence. Ncibi et al (2021) investigated the efficacy of natural products that were discovered to be safe for adult honeybees while effectively controlling fourth instar wax moth larvae.…”
Section: Accumulative Corrected Mortality (%) Of Some Essential Oils ...mentioning
confidence: 93%
“…Fourth instar larvae of the G. mellonella treated with Menthapiperita, Pelargonium graveolens L. and Ocimumbasilicum L. decrease pupation and percentage of adult emergence and extended the larval-pupal periods. In terms of mortality, O. basilicum is the most active, followed by M. piperita and finally, P. graveolens (Elbarky et al 2015). The oils of five plants (neem, cedar, clove, peppermint, and karang) and one extract (neem seed kernel) were tested at various concentrations and exhibited varying degrees of activity against the larvae of G. mellonella.…”
Section: Introductionmentioning
confidence: 99%